Complement Factor H-Related Proteins FHR1 and FHR5 Interact With Extracellular Matrix Ligands, Reduce Factor H Regulatory Activity and Enhance Complement Activation - Papp, Alexandra; Papp, Krisztián; Uzonyi, Barbara; Cserhalmi, Marcell; Csincsi, Ádám I.; Szabó, Zsóka; Bánlaki, Zsófia; Ermert, David; Prohászka, Zoltán; Erdei, Anna; Ferreira, Viviana P.; Blom, Anna M.; et al. (Frontiers in Immunology, 2022)
Components of the extracellular matrix (ECM), when exposed to body fluids may promote local complement activation and inflammation. Pathologic complement activation at the glomerular basement membrane and at the Bruch’s membrane is implicated in renal and eye diseases, respectively. Binding of soluble complement inhibitors to the ECM, including factor H (FH), is important to prevent excessive complement activation. Since the FH-related (FHR) proteins FHR1 and FHR5 are also implicated in these diseases, our aim was to study whether these FHRs can also bind to ECM components and affect local FH activity and complement activation. Both FH and the FHRs showed variable binding to ECM components. We identified laminin, fibromodulin, osteoadherin and PRELP as ligands of FHR1 and FHR5, and found that FHR1 bound to these ECM components through its C-terminal complement control protein (CCP) domains 4-5, whereas FHR5 bound via its middle region, CCPs 3-7. Aggrecan, biglycan and decorin did not bind FH, FHR1 and FHR5. FHR5 also bound to immobilized C3b, a model of surface-deposited C3b, via CCPs 3-7. By contrast, soluble C3, C3(H2O), and the C3 fragments C3b, iC3b and C3d bound to CCPs 8-9 of FHR5. Properdin, which was previously described to bind via CCPs 1-2 to FHR5, did not bind in its physiologically occurring serum forms in our assays. FHR1 and FHR5 inhibited the binding of FH to the identified ECM proteins in a dose-dependent manner, which resulted in reduced FH cofactor activity. Moreover, both FHR1 and FHR5 enhanced alternative complement pathway activation on immobilized ECM proteins when exposed to human serum, resulting in the increased deposition of C3-fragments, factor B and C5b-9. Thus, our results identify novel ECM ligands of FH family proteins and indicate that FHR1 and FHR5 are competitive inhibitors of FH on ECM and, when bound to these ligands, they may enhance local complement activation and promote inflammation under pathological conditions.